Differences in locomotor gross motor development level among grade 1 ballet dancers, students with and without co-curricula - Abdullah, Borhannudin; Joseph, Jacklyn; Mohd Saleh, Maisarah (University of Pitesti, Romania, 2016)
Purpose: The study is a survey form ex post facto and the purpose of this study was to identify the level of locomotor skills among grade one ballet dancers, students with co-curriculum and students without co-curriculum.